2008
DOI: 10.1016/j.tips.2008.02.004
|View full text |Cite
|
Sign up to set email alerts
|

How and why do GPCRs dimerize?

Abstract: Dimerization is fairly common in the G-protein-coupled receptor (GPCR) superfamily. First attempts to rationalize this phenomenon gave rise to an idea that two receptors in a dimer could be necessary to bind a single molecule of G protein or arrestin. Although GPCRs, G proteins and arrestins were crystallized only in their inactive conformations (in which they do not interact), the structures appeared temptingly compatible with this beautiful model. However, it did not survive the rigors of experimental testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
143
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(146 citation statements)
references
References 69 publications
(146 reference statements)
3
143
0
Order By: Relevance
“…They revealed the kinetics of complex formation, indicating that GPCR can form either stable or transient complexes at the cell surface depending on the interaction energy (Gurevich and Gurevich, 2008). To exist as a stable dimer with a halflife comparable to that of even short-lived GPCR (2-20 h), a binding energy of at least ~60 kJ/mol is required.…”
Section: Quaternary Structure Of Gpcr Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…They revealed the kinetics of complex formation, indicating that GPCR can form either stable or transient complexes at the cell surface depending on the interaction energy (Gurevich and Gurevich, 2008). To exist as a stable dimer with a halflife comparable to that of even short-lived GPCR (2-20 h), a binding energy of at least ~60 kJ/mol is required.…”
Section: Quaternary Structure Of Gpcr Complexesmentioning
confidence: 99%
“…Furthermore, in view of the fact that the three above-mentioned class A GPCRs shown to be functional as monomers also exist as dimers or higher-order oligomers (see below), the existence of class A GPCR functional oligomers cannot be excluded (see Franco et al, 2016, for a recent discussion of the topic). In this respect, of interest are studies showing that class A receptors appear to exist in a monomer-dimer equilibrium, where class A GPCR dimers are often transient as seen from their half-lives determined from the rate of association and dissociation (Gurevich and Gurevich, 2008). This may help explain opposing views on the role of class A GPCR monomers versus dimers (Chabre and le Maire, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the crystal structure of the chemokine CXCR4 receptor dimer (Wu et al, 2010) reported receptor interfaces at TM5 and TM6. In contrast to homomeric receptor complexes, the receptor interface(s) involving class A GPCR heteromers does not appear to rely predominantly on TM interactions, resulting in concern as to whether the binding energy between the receptors in these heteromers is actually sufficient to result in stable long-lasting physical interactions (Gurevich and Gurevich, 2008). However, it has been demonstrated in several examples that certain amino-acid residues, specifically two or more adjacent arginines on one protomer and two or more adjacent glutamic acids, or aspartic acids, or a phosphorylated residue on the other protomer, is sufficient to induce the formation of stable non-covalent complexes (Jackson et al, 2006;Woods and Ferré, 2005).…”
Section: The Receptor Interface: Receptor Homomers Versus Receptor Hementioning
confidence: 99%
“…The functional role of such supra-molecular complexes is still unclear and may vary depending on the GPCR type [18,20]. In particular, for TP, the formation of TPa-TPb and TPa-IP heterodimers in constitutive human systems seems to greatly influence their pharmacological profiles [4][5][6], whereas no data are yet available on the functional significance of TP homodimerization.…”
Section: Discussionmentioning
confidence: 99%
“…The conformational changes transmitted by direct proteinprotein interactions may represent a first level of regulation of a receptor. The biological role(s) of homologous and heterologous receptor aggregation is/are, however, far from being clarified [18][19][20]. Likewise, knowledge about the most likely architectures of GPCR dimers is still illdefined.…”
Section: Introductionmentioning
confidence: 99%